Science and philosophy in the Indian Buddhist classics - Jinpa, Thupten; Rochard, Dechen; Dunne, John D.; Compendium Compilation Committee (New Delhi : Simon and Schuster India, 2020)
"The second volume in a prominent new series on Buddhism and science, directed by the Dalai Lama and previously covered by the BBC. Science and Philosophy in the Indian Buddhist Classics compiles classical Buddhist explorations of the nature of our material world, the human mind, logic, and phenomenology and puts them into context for the modern reader. This ambitious four-volume series$1 (Ba major resource for the history of ideas and especially the history of science and philosophy$1 (Bhas been conceived by and compiled under the visionary supervision of His Holiness the Dalai Lama himself. To present specific ideas and their rationale, the volume weaves together passages from the works of great Buddhist thinkers like Asanga, Vasubandhu, Nagarjuna, Dignaga, and Dharmakirti. His Holiness the Dalai Lama$1 (Bs introduction outlines scientific and philosophical thinking in the history of the Buddhist tradition. To provide additional context for Western readers, each of the six major topics is introduced with an essay by John D. Dunne, distinguished professor of Buddhist philosophy and contemplative practice at the University of Wisconsin. These essays connect the traditional material to contemporary debates and Western parallels, and provide helpful suggestions for further reading."--s
Keywords: Matter--Religious aspects--Buddhism; Buddhist philosophy; Buddhist literature